2009
DOI: 10.1126/science.1169041
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Infrared Detection of Cyanide Flip on Silver-Alumina NO x Removal Catalyst

Abstract: Spectroscopic studies of the mechanistic steps that occur on supported precious metal catalysts used in industrial and automotive applications are hampered by a dearth of suitable experimental methods. We used femtosecond laser excitation followed by nanosecond time-resolved in situ Fourier-transform infrared spectroscopy to initiate a catalytic reaction on alumina-supported silver catalysts, which are of interest in minimizing nitrogen oxide emissions from fuel-efficient lean-burn engines. We found that the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 28 publications
2
77
1
Order By: Relevance
“…The characteristic IR peaks of -NCO located around 2230 and 2250-2260 cm À1 have been commonly observed on Ag/Al 2 O 3 during HC-SCR, while the assignments of their coordination sites are still controversial. Bion et al 191,192 and Thibault-Starzyk et al 196 observed the characteristic frequencies of -NCO on Ag/Al 2 O 3 located at 2255-2265 and 2228-2240 cm À1 , which were assigned to -NCO species coordinated with octahedral Al 3+ ions (Al VI -NCO) and tetrahedral Al 3+ sites (Al IV -NCO), respectively. During the reduction of NO x with ethanol and propene on , and ÀNCO (n) for the cases of (A), and (C), respectively, and (E) time dependence of N 2 and CO 2 concentration calculated from the mass signals for the cases of (C).…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 97%
See 1 more Smart Citation
“…The characteristic IR peaks of -NCO located around 2230 and 2250-2260 cm À1 have been commonly observed on Ag/Al 2 O 3 during HC-SCR, while the assignments of their coordination sites are still controversial. Bion et al 191,192 and Thibault-Starzyk et al 196 observed the characteristic frequencies of -NCO on Ag/Al 2 O 3 located at 2255-2265 and 2228-2240 cm À1 , which were assigned to -NCO species coordinated with octahedral Al 3+ ions (Al VI -NCO) and tetrahedral Al 3+ sites (Al IV -NCO), respectively. During the reduction of NO x with ethanol and propene on , and ÀNCO (n) for the cases of (A), and (C), respectively, and (E) time dependence of N 2 and CO 2 concentration calculated from the mass signals for the cases of (C).…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 97%
“…29,178,[191][192][193][194][195][196][197] With this in mind, the relationship between -NCO formation and the consumption of enolic species and acetate was investigated on Ag/Al 2 O 3 via the transient response of the DRIFTS method, and typical results are presented in Fig. 5.…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 99%
“…Simultaneously, enolic species (1633 cm Fig. 3 (continued) [5,6,9,[32][33][34][35][36]. The peak at 1591 cm À1 can be assigned to formate species.…”
Section: Steady State In Situ Drifts Study Of the Scr Of Nox By C4 Almentioning
confidence: 99%
“…Switching the feed gas to NO + O 2 resulted in a sharp decrease in the intensity of enolic species and acetate. A new peak of ANCO appeared at 2229 cm À1 [5,6,9,[32][33][34][35][36], and its intensity increased with time on stream, reaching a maximum at 3 min and then decreasing gradually. After the flowing of NO + O 2 for 10 min, the enolic species decreased slowly and the intensity of the ANCO peak significantly decreased.…”
mentioning
confidence: 99%
“…4 The next step in the reaction mechanism is the reaction between the adsorbed NO x and the partially oxidized carbonaceous species forming organic nitrites and nitro species (R-NO 2 ), amino species (R-NH 2 ), surface bound cyanide (-CN), and isocyanate species (-NCO). Nanosecond timeresolved IR studies have shown that silver-bound cyanide species flip to the alumina surface, forming isocyanate species in the presence of CO and NO on a silver alumina catalyst, 28 whereas other studies with propene have indicated that the cyanide and isocyanate species might belong to two parallel pathways, where cyanides belong to a minor reaction route and isocyanates are part of the major route formed from surface nitrates and carbonaceous species. 29 The organic nitrites, nitro, amino species, cyanide, and isocyanate species readily react with water-forming ammonia that can reduce surface-bound or gaseous NO x to N 2 .…”
Section: Introductionmentioning
confidence: 99%